(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: This article explores a tricky idea: moral relativism. It looks at what it means, the different forms it takes, and the arguments for and against it. We’ll examine how it affects us as individuals, our societies, and whether we can even agree on any moral rules. It’s a balancing act: respecting different views versus the danger of saying harmful things are okay just because a culture accepts them.